The comparison of several cryptosystems using the elliptic curve: a report - Trung, Mai Manh; Do, Le Phe; Tuan, Do Trung; Trieu, Thu Thuy; Tanh, Nguyen Van; Tri, Ngo Quang; Cong, Bui Van (Institute of Advanced Engineering and Science, 2024)
The elliptic curve cryptosystem (ECC) has several applications in Information Security, especially in cryptography with two main activities including encrypting and decrypting. There were several solutions of different research teams which propose various forms of the elliptic curve cryptosystem on cryptographic sector. In the paper, we proposed a solution for applying the elliptic curve on cryptography which is based on these proposals as well as basic idea about the elliptic curve cryptosystem. We also make comparison between our proposal and other listed solution in the same application of the elliptic curve for designing encryption and decryption algorithms. The comparison results are based on parameters such as time consumption (t), RAM consumption (MB), source code size (Bytes), and computational complexity.